Implementasi Pembelajaran Penjas Pada Masa Pandemic Covid-19 Dikelas Vi Sd Se-Kecamatan Karangampel - Anang Setiawan; Khoerul Anwar; Seni Oktriani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to determine the implementation of Physical Education, Sports, and Health learning during the COVID-19 pandemic in grade VI SD in Karangampel District, Indramayu Regency, West Java Province. This study uses a quantitative descriptive research design with a one shot case study approach using a survey method. The sampling technique used incidental sampling technique. The samples in this study were physical education teachers, students and students of class VI SD and parents of students who live in Karangampel sub-district. The sample consisted of 67 people consisting of 5 sports teachers, 45 elementary school sixth grade students and 17 students' parents. The instrument in this study was an online questionnaire using a google form containing 15 questions. The data analysis technique used quantitative descriptive analysis with percentage data processed using Microsoft Excel.Based on the results of the study, it can be concluded that the impact during the COVID-19 pandemic changed the implementation of Physical Education learning in grade VI elementary schools throughout the Karangampel sub-district, Indramayu district into online and combined learning (online and face-to-face).